Citizenship Education: Toward a Relationality and Care Approach - Shehneh, Shaima (Journal of Ethnic and Cultural Studies, 2024)
Responding to public rhetoric and policy documents advocating for citizenship education as the type of education that will safeguard democracy and address societal challenges, schools around the world have been including citizenship education as a discrete part of the curriculum. While the field remains complex and contextual, some of the major aims maintain the cultivation of a critical, active, responsible, democratic citizen. In this paper, I explore apolitical and exclusionary approaches to citizenship education by problematizing terms such as participation, human rights, autonomy, and critical thinking. Through emphasizing the citizen-in-context, I draw on Biesta’s notion of subjectification to approach citizenship education in a pluralistic society. In challenging a universal neutral framework of human rights, I propose citizenship as care and relationality to defy exclusion and unjust dominant discourses and practices in the field. I also reflect on my own personal journey as a researcher from the periphery, conducting research in and on the center. I bring in some memos and journals that highlight some tensions and struggles as well as channels of emancipation and relief.